The Effect Of Capital Structure, Firm Size, and Inventory Turnover on Profit Growth (Empirical Study of Coal Mining Companies Listed on The BEI in 2021-2023) - Muhammad Fachri; Aira, Aras (MUI Kota Pekanbaru, 2024)
This study aims to determine the effect of capital structure, firm size, and inventory turnover on profit growth. This research is a quantitative research. This research was conducted on coal mining companies listed on the Indonesia Stock Exchange in 2021- 2023. The population in this study amounted to 28 companies, using a purposive sampling method, a sample of 13 companies was determined for 3 years of observation so that the total observation data was 39 reports. Data analysis in this study used panel data regression with the help of Eviews. The processing results are according to the model selection test, concluding the data using a random effect model, while the results of hypothesis testing show that capital structure, firm size and inventory turnover have a significant influence on profit growth. Meanwhile, simultaneously capital structure, firm size and inventory turnover influence profit growth. The result of the adjusted rsquared coefficient of determination is 0.780802. This explains the contribution of the capital structure, firm size and inventory turnover variables in this study explaining 78.08% of the variation in the profit growth variable. Meanwhile, the remaining 21.92% is influenced by other variables not measured in this regression model.